2017
DOI: 10.1007/s11356-017-8773-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptional analysis of cardiovascular-related genes and pathways induced by PM2.5 in human myocardial cells

Abstract: Air pollution has been a major environment-related health threat. Most of the studies on PM toxicity have verified on the cardiovascular system and endothelial cells. However, researches on PM-induced myocardial-related toxicity are limited. This study aims to fully understand the toxic effects of PM on human myocardial cell (AC16) and explore its molecular mechanism based on microarray analysis and bioinformatics analysis. Microarray data analysis manifested that PM-induced toxicity affected expression of 472… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 35 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…Our results demonstrated that cell differentiation and maturation, cell-cell signaling, and signal transduction involved in the immune response were the main molecular and cellular functions of genes, which were enriched in the AP group. The findings from the present study also confirm the findings of several other reports, which have suggested that TGF-β signaling was regulated after exposure to PM2.5 18 20 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results demonstrated that cell differentiation and maturation, cell-cell signaling, and signal transduction involved in the immune response were the main molecular and cellular functions of genes, which were enriched in the AP group. The findings from the present study also confirm the findings of several other reports, which have suggested that TGF-β signaling was regulated after exposure to PM2.5 18 20 .…”
Section: Discussionsupporting
confidence: 92%
“…Eukaryotic translation initiation factor 5B, or Eif5b , has been previously studied in the area of toxicity. Human myocardial cells which underwent PM2.5‐induced myocardial‐related toxicity showed a confirmed decrease in Eif5b expression (Feng et al, 2017). This may also support the severity of the disease manifestation in females.…”
Section: Discussionmentioning
confidence: 99%
“…Another significant site located 0.3 kb downstream of the BRIX1 (Biogenesis of ribosomes BRX1) gene on the Z chromosome was found. BRIX1 (ribosomal biogenesis protein BRX1) is a protein-coding gene associated with the gastric cancer network pathway and neural development of the chicken brain [37].…”
Section: Discussionmentioning
confidence: 99%